Students' Learning Difficulties in Balinese Language Subjects in Grade IV of Elementary School : Kesulitan Belajar Siswa Pada Mata Pelajaran Bahasa Bali Kelas IV Sekolah Dasar - Komang Puteri Yadnya Diari; Insani2, Nur Hanifah (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
Abstract This study aims to identify students' learning problems in the Balinese language subject in one of the Elementary Schools (SD) in Bali. To achieve the focus of the study, the researcher used a descriptive qualitative case study research method. The subjects of this study were one 4th grade elementary school teacher and 28 students. The data collection methods used in this study were observation, interviews, and documentation. The analysis used in this study was Miles and Huberman. Based on the results of the study, as many as 28 4th grade elementary school students experienced learning difficulties known as learning difficulties in understanding concepts. Then there are several factors that cause students to experience learning difficulties in the subject. Among them are teachers who do not use enough learning media, and students who feel bored in the Balinese language subject. Abstrak Penelitian ini bertujuan mengidentifikasi masalah belajar siswa pada mata pelajaran Bahasa Bali pada salah satu Sekolah Dasar (SD) di Bali. Peneliti menggunakan metode penelitian kualitatif deskriptif studi kasus untuk mencapai fokus penelitian. Satu guru di kelas 4 SD dan 28 siswa adalah subjek penelitian ini. Penelitian ini menggunakan observasi, wawancara, dan dokumentasi untuk mengumpulkan data. Penelitian ini menggunakan analisis Miles and Huberman. Seperti yang ditunjukkan oleh hasil penelitian, 28 siswa di kelas 4 SD mengalami kesulitan belajar, yang dikenal sebagai kesulitan belajar dalam memahami konsep. Kemudian ada beberapa faktor yang menyebabkan siswa mengalami kesulitan belajar di bidang tersebut. Ini termasuk guru yang tidak menggunakan media pembelajaran, dan siswa yang merasa bosan dalam mata Pelajaran Bahasa Bali.